Bioactive Restorative Materials in Modern Dentistry: A Comprehensive Review of Remineralization Potential and Clinical Performance (Bangladesh Journal of Medical Science, 2026)
Bioactive restorative materials have become increasingly important in modern minimally invasive dentistry because they are designed not only to replace lost tooth structure but also to interact with the surrounding oral environment. Unlike conventional inert restorative materials, bioactive systems may release fluoride, calcium, phosphate, strontium, silicate, or alkaline ions, thereby promoting remineralization, buffering acidic biofilm conditions, and potentially reducing secondary caries. This narrative review summarizes current knowledge regarding the mechanisms, laboratory evidence, clinical performance, limitations, and future directions of bioactive restorative materials. The review focuses on glass-ionomer cements, resin-modified glass ionomers, giomers, alkasites, bioactive resin composites, calcium silicate-based materials, and bioactive glass-modified systems. The available evidence suggests that ion-releasing materials can support remineralization under controlled in vitro or in situ conditions, particularly when demineralized dentin or enamel is exposed to repeated acidic challenges. Clinical evidence is more heterogeneous. Glassionomer and resin-modified glass-ionomer materials show meaningful advantages in high-caries-risk patients and pediatric dentistry, whereas bioactive resin composites and alkasites often demonstrate clinical performance comparable to conventional composites but not consistently superior longevity. Failure patterns are influenced by moisture control, marginal adaptation, mechanical loading, adhesive compatibility, material solubility, and patient-level caries risk. Current evidence supports selective use of bioactive materials as part of comprehensive caries management rather than as stand-alone substitutes for prevention. Future research should standardize definitions of bioactivity, include long-term randomized trials, and integrate biological outcomes with restoration survival.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S223-S228